A Correlational Study Investigating Students’ Activities in STAD Model and Their Interest in Learning English - Albiansyah, A; Hardiyanti, Endah (CV. Inara, 2020)
Abstract. The study attempts to know the significant correlation between students’ Activities in STAD Model and their interest in learning English. This study was a correlational study designed to determine whether and how a set of variables had related to each other. The participants were 50 students in the first year of high school. The instruments used in this study were observation sheet and questionnaire. Observation sheet is used to find out the category of students’ activities in STAD model and give a questionnaire consisting of seven items to the students. SPSS was used to analyze the data. The score of product-moment by using SPSS, Rxy is (0,410): it showed there was a significant correlation between students’ activities in STAD model and their interest in learning English. Referring to the product-moment table, it shows that the correlation is “enough” because 0,401 placed between 0,400 – 0,599. In addition, the null hypothesis was rejected because r table is lower than r observation whether at 5% (0,279) or at 1 % (0,361) level of significance, meaning that there was a significant correlation between students’ activities in STAD model and their interest in learning English. So, it can be concluded that activities in STAD model can influence students’ interest because, in STAD model, students can learn the English learning material better. . Keywords: Students’ activities, STAD model, interest, learning English.